Moroccan Foreign Policy in sub-Saharan Africa - (:unkn) unknown (My University, 2013)
Morocco’s history is closely tied to sub-Saharan Africa. For many centuries, the country experienced vivid exchanges with the rest of the continent. This pattern radically changed by the 19th century, with European colonialism effectively cutting Moroccan links with sub-Saharan Africa and shifting the country’s economic interests northwards. The legacy of colonialism had a considerable influence in shaping contemporary Moroccan foreign relations. Indeed, since its independence in 1956, Rabat focused much of its efforts on building its relations with Europe and North America whereas generally disregarding sub-Saharan Africa. In this paper I re-explore the history of Moroccan foreign policy with sub-Saharan Africa in the post-independence period. I argue that while Morocco initially gave little attention to sub-Saharan Africa, the Western Sahara stalemate in the 1990s resulted in changing Rabat’s strategy vis-à-vis the rest of the continent. With the priority to secure Rabat’s territorial interests, Morocco started ever since investing massive efforts in (re)building its ties with sub-Saharan Africa.
Keywords: African Research